A Critical Analysis On Margaret E. Roberts (2018), Censored: Distraction And Diversion Inside China’s Great Firewall - Rahayu, Restu Karlina (Journal of Political Issues, 2020)
Margaret E. Robert book builds on a foundation of the basic law of economy which is the relationship between supply and demand. She argues that censorship Chinese government censorship has violated free market law. In her book, she specified three mechanisms of censorship; fear, friction, and flooding (Roberts 2018). She explained in detail how Chinese’s people reactions toward the censorship in chapter four, five and six. In this paper, I challenged Roberts idea that fear is not part of the censorship mechanism. I have two arguments; first fear is emotion it needs stimuli to appear. Second fear and curiosity are motivation behind information seeking. Fear appeared from negative experience while curiosity appeared from positive outcomes. Fear is part of information behavior, it works like a brake system (Heinstrom 2010). Through fear, the disappointment and punishment will be evaluated by individuals to decide the next move. Fear is something dynamic, as time evolve it creates sensitivity, but it does not stop the basic need of information. American astronaut Thomas P. Stafford mentioned that evolution made us the ultimate learning machine, and the ultimate learning machine needs to be oiled by curiosity (Stafford 2012). At the end of my paper, I suggested Roberts to consider using word threat as one of censorship mechanism rather than fear.